Development of Self-Regulation Model Based on Health Promotion Model on Anemia Prevention Behavior in Pregnant Women - Mira Triharini; Kusnul Chotimah; Praba Diyan Rachmawati; Eka Mishbahatul Mar’ah Has (Poltekkes Kemenkes Surakarta, 2025)
Background: Anemia prevention in pregnant women is essential to reduce health risks for both mother and fetus. This study aimed to develop a self-regulation model for anemia prevention behavior based on the Health Promotion Model. Methods: An explanatory design with a cross-sectional approach was applied to 115 pregnant women attending health centers in Surabaya, selected through cluster sampling. Data were collected using a structured questionnaire and analyzed using SEM-PLS. Results: The findings showed that anemia prevention behavior was significantly influenced by behavioral self-regulation (T=2.945) through personal regulation (T=5.932), which was shaped by environmental self-regulation (T=8.611) and individual characteristics (T=3.302). Commitment did not directly affect anemia prevention behavior (T=0.144; p=0.886). The model demonstrated substantial explanatory power, with R² values of 71.9% for behavioral self-regulation and 43.1% for anemia prevention behavior. Predictive relevance (Q² > 0) confirmed the model’s robustness across different contexts. Conclusion: This study highlights the pivotal role of self-regulation processes in shaping anemia prevention behavior. The model can serve as a framework for nursing interventions to strengthen self-regulation among pregnant women and improve maternal and fetal health outcomes.